Reversible Thrombocytopenia after Gabapentin in an HIV-Positive Patient - Mohammed Basith; Andrew Francis; Alfredo Bellon (Case Reports in Psychiatry)
Gabapentin has become increasingly used in psychiatric practice specifically for anxiety disorders. Even though gabapentin is not approved by the US Food and Drug Administration to treat anxiety, physicians sometimes use it as an alternative to benzodiazepines in patients with a history of substance abuse. Gabapentin is also prescribed when individuals are at risk of thrombocytopenia which is not considered a side effect. Among patients at risk of thrombocytopenia are those positive for human immunodeficiency virus (HIV). Here we present a case of an HIV-positive man who presented for inpatient psychiatric care with severe anxiety and a history of alcohol and benzodiazepine abuse. In this patient, gabapentin worsened thrombocytopenia after repeated exposure to this medication. We suggest caution when considering gabapentin for patients with preexisting low platelet counts, as there seems to be a risk for worsening thrombocytopenia with this antiepileptic in the presence of HIV infection.